2020
DOI: 10.1111/hel.12730
|View full text |Cite
|
Sign up to set email alerts
|

The increasing antimicrobial resistance of Helicobacter pylori in Iran: A systematic review and meta‐analysis

Abstract: Background Antimicrobial resistance of Helicobacter pylori can result in eradication failure. Metadata on the antimicrobial resistance of H pylori in Iran could help to formulate H pylori eradication strategies in Iran. Methods A systematic review was performed after searching in MEDLINE, Scopus, Embase, Web of Science, and the Cochrane Library. A meta‐analysis was performed, and a comparison of the rates between children and adults; time periods (1999‐2010, 2011‐2016, 2017‐2019); and the methods used was carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…In a review conducted in Iran in 2015 [30] to evaluate the resistance of H. pylori, out of 1553 samples, 956 samples (61.6%) showed resistance to metronidazole. In 2017 [29], out of 926 samples, 58% were resistant to metronidazole, and finally in 2020 [31], out of 4330 samples, 62% of the samples were resistant to this antibiotic. This indicates the relatively stable resistance of H. pylori in recent years in Iran.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a review conducted in Iran in 2015 [30] to evaluate the resistance of H. pylori, out of 1553 samples, 956 samples (61.6%) showed resistance to metronidazole. In 2017 [29], out of 926 samples, 58% were resistant to metronidazole, and finally in 2020 [31], out of 4330 samples, 62% of the samples were resistant to this antibiotic. This indicates the relatively stable resistance of H. pylori in recent years in Iran.…”
Section: Discussionmentioning
confidence: 98%
“…The prevalence of H. pylori resistance to amoxicillin and tetracycline in different geographical areas is 0-30% and 0-10%, respectively [34]. With increasing antibiotic resistance of H. pylori, it is recommended to replace the treatment of quadruple bismuth (treatment including proton-pump inhibitor (PPI), bismuth, metronidazole, and tetracycline) with a triple treatment based on clarithromycin in the first line of eradication of H. pylori [31]. Molecular genetic testing may estimate the prevalence of resistance higher than phenotypic testing because it more accurately detects populations mixed with resistant and sensitive kettles although the unclear clinical relevance of heteroresistance should be [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…[58][59][60]73,74 However, studies have revealed alarmingly high amoxicillin resistance rates exceeding 15% in Iran, which suggests the need for cautious application of the HDDT regimen in such regions. 75 In situations characterized by low amoxicillin resistance, meticulous consideration must be given to the dosage of amoxicillin when implementing dual therapy. An RCT conducted in China compared the effectiveness of a low-dose dual therapy with a HDDT in treatment-naïve patients (vonoprazan 20 mg and amoxicillin 1000 mg, administered either twice daily or thrice daily).…”
Section: Susceptibility Testing In Hddtmentioning
confidence: 99%
“…pylori strains 58–60,73,74 . However, studies have revealed alarmingly high amoxicillin resistance rates exceeding 15% in Iran, which suggests the need for cautious application of the HDDT regimen in such regions 75 …”
Section: The Application Of Susceptibility Testingmentioning
confidence: 99%
“…According to existing reports, the TET‐resistance rate in H. pylori is generally at a low level in most regions of the world. In Asia, it has been reported that the TET‐resistance rates are 1.18% in China, 12 0.6% in Bhutan, 89 8% in Iran, 90 5.3% in India, 63 and 2% in Japan 11 . In Europe, the total TET‐resistance rate was below 1%, 14 and that in Germany was 2.5% 66 .…”
Section: Resistance Profiles and Biomolecular Mechanisms Of Single‐dr...mentioning
confidence: 99%